THE PROFILE OF COGNITIVE FUNCTION OF PATIENTS HIV/AIDS IN Dr. SAIFUL ANWAR MALANG HOSPITAL - Harahap, Herpan Syafii; Rianawati, Sri Budhi (Malang Neurology Journal, 2015)
Background. HIV/AIDS caused cellular immunodeficiency (the depletion of CD4+). This, in turn, raised many complications, such as HIV-associated dementia (HIV-D).Objective. To know the profile of cognitive function of patients of HIV/AIDS tretaed in Dr. Saiful Anwar Malang Hospital.Methods. This was a descriptive study using cross-sectional design. This study was conducted to 41 patients of HIV/AIDS treated in Dr. Saiful Anwar Malang Hospital during January to February 2012 (n=41). The cognitive function was assessed by using Mini Mental State Examination (MMSE) and Clock Drawing Test (CDT) instruments.Results. In MMSE, Number of patients showing total score 0-16 were 9 (21.95%), those showing total score 17-23 were 25 (60.98%), and those showing total score 24-30 were 7 (17.07%) . In CDT, 37 patients showed decrease of cognitive function (CDT<4), the remainder showed normal cognitive function. All of patients showing total score of both MMSE and CDT below normal limit, showed low level of CD4 (< 200 sel/µL). Patients showing normal cognitive function on CDT, also showing the same result on MMSE.Conclusion. Most of patients in this study showed the decrease of cognitive function.